2010
DOI: 10.1111/j.1464-410x.2010.09691.x
|View full text |Cite
|
Sign up to set email alerts
|

Do men with mild erectile dysfunction have the same risk factors as the general erectile dysfunction clinical trial population?

Abstract: versus 55 ± 11 (18-89) years, body mass index was 29 ± 5 (20-48) versus 28 ± 5 (11-64) kg/m 2 and ED duration was 3.5 ± 3.2 ( < 1-18) versus 4.6 ± 4.7 ( < 1-45) years.• The prevalence of comorbidities associated with ED was similar (hypertension 26.1% ( n = 46) vs 32.8%; diabetes mellitus 13.6% ( n = 24) vs 22.1%; dyslipidemias 12.5% ( n = 22) vs 11.7%; hypercholesterolemia 12.5% ( n = 22) vs 9.5%; gastro-esophageal reflux disease 10.8% ( n = 19) vs 6.0%; benign prostatic hyperplasia 9.7% ( n = 17) vs 9.9%; de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 28 publications
3
17
0
2
Order By: Relevance
“…De erectiele functie en het cardiovasculaire systeem worden op gelijke wijze gereguleerd door het sympathische en parasympathische deel van het autonome zenuwstelsel. Vasculaire ED kan helpen bij het ontdekken van CVZ in een vroege fase [5], maar of ED ten gevolge van autonome disregulatie een toekomstige cardiovasculaire autonome neuropathie kan voorspellen, blijft nog onduidelijk.…”
Section: De Autonome Regulatieunclassified
See 1 more Smart Citation
“…De erectiele functie en het cardiovasculaire systeem worden op gelijke wijze gereguleerd door het sympathische en parasympathische deel van het autonome zenuwstelsel. Vasculaire ED kan helpen bij het ontdekken van CVZ in een vroege fase [5], maar of ED ten gevolge van autonome disregulatie een toekomstige cardiovasculaire autonome neuropathie kan voorspellen, blijft nog onduidelijk.…”
Section: De Autonome Regulatieunclassified
“…Cardiovasculaire en metabole ziekten (CVMZ) hebben een zeer sterke link met ED, en talrijke studies hebben deze associatie aangetoond [4,5]. Zo toonde Montorsi in 2003 aan dat ED vooraf kan gaan aan cardiovasculaire ziekten (CVZ): bij 300 patiënten met acute pijn op de borst met vervolgens angiografisch bewezen atherosclerose van de coronaire arteriën, was reeds in 49 % van de gevallen vooraf sprake van ED en in 67 % van de gevallen trad ED op voorafgaand aan klachten van CVZ [4].…”
unclassified
“…In contrast, some studies have demonstrated that the prevalence of cardiovascular comorbidities in men with mild ED was comparable to that in men with more severe ED [8,9,11]. Despite the potential relationships between ED and cardiovascular diseases, men with mild ED do not appear to seek or receive appropriate medical care because of attitudes, beliefs, or other psychological factors [11,12]. More importantly, investigations have been scarce for the association between mild ED and cardiovascular diseases [11].…”
Section: Introductionmentioning
confidence: 99%
“…One study reported that only moderate-to-severe ED, but not mild ED, was associated with increased risk for coronary heart diseases or cerebrovascular stroke within 10 years [3]. In contrast, some studies have demonstrated that the prevalence of cardiovascular comorbidities in men with mild ED was comparable to that in men with more severe ED [8,9,11]. Despite the potential relationships between ED and cardiovascular diseases, men with mild ED do not appear to seek or receive appropriate medical care because of attitudes, beliefs, or other psychological factors [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation